0.33(9-2x)=x+1

Simple and best practice solution for 0.33(9-2x)=x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.33(9-2x)=x+1 equation:



0.33(9-2x)=x+1
We move all terms to the left:
0.33(9-2x)-(x+1)=0
We add all the numbers together, and all the variables
0.33(-2x+9)-(x+1)=0
We multiply parentheses
-0.66x-(x+1)+2.97=0
We get rid of parentheses
-0.66x-x-1+2.97=0
We add all the numbers together, and all the variables
-1.66x+1.97=0
We move all terms containing x to the left, all other terms to the right
-1.66x=-1.97
x=-1.97/-1.66
x=1+0.31/1.66

See similar equations:

| 2x+20-4x=90 | | 8x+10=3x-95 | | -23=-1+8x+3x | | 8=x(7-2) | | 32=(1.8×c)+32 | | -2(x+2)=-10-4x | | -26=-6-6a | | 5x=7×+4 | | 6x-1=54 | | 2(-6+8)=x-3/2 | | 8x+7(2-3x)=-6(6x+5) | | -10j+18=-7j | | -8-16w=-17w-1 | | (2.1(2.3+2.1x)=11.65+x)100 | | x+12+2x+29+x+5=180 | | -8-16w=-17-1 | | -7(x+2)=-2(3x-2)+7x | | 2u-7=4u-1 | | 5m=7m+6 | | 2+13+9-3+x=180 | | 3h=5h+10 | | 5x+2(5x-4)=-83 | | -10t-8=-8-6t | | 2+13+9-3+x=90 | | 5(v+1)-v=4(v-1)-9 | | 6x-4(-2x-22)=24 | | 5+4r=3r | | 64x-6=34x-16 | | 4x+1+9x-3=90 | | 2-v=5v+20 | | 6-3f=-5f | | 7-3b=-4b |

Equations solver categories